Role of Demographics Factors on Organization Commitment of Restaurant Workforce (Pravaha, 2023)
The dedication of employees to the organization is a significant component in determining its overall health. Additionally, the demographic makeup of the workforce influences the degree of commitment. So considering the situation the study examined the how demographic factors affect the level of commitment towards their organization. The population of the study was employees working in restaurant situated in Lalitpur district of Bagmati Zone. One hundred and fifty-four restaurant workforce were taken as the sample for the study. Convenience sampling was used to gather the information regarding organizational commitment from concerned respondents. Valid organization commitment questionnaire OCQ was employed to test the organizational commitment of restaurant workforce. The analytical research design was used to examine the influence of demographic factors. The statistical test used in the study were percentage frequency, independent sample t test and one-way ANOVA. The internal consistency of the OCQ was found reliable with Cronbach alpha (α = 9.33).  The result revealed that only two demographic factors (income, job position) were found to be influencing factors for determining organizational commitment level. The remaining factors (like age, marital status, service years, education, gender) did not seem important factor to affect the organizational commitment. So the owner of the restaurants will get benefit form the result of the study and stay focused on the how income and their promotion can be important for getting committed employees in the organizations. Regarding limitation of the study, area coverage is small so future researcher is suggested to go beyond this area to make their result generalizable.